Driving Green Economy for Malaysia through Green Technology and Green Culture - Zainul Abidin, M.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
In the world we live in today, issues of climate change and the need for sustainable solutions have become more prominent. During the agreement reached in Paris in December 2015, the world was unanimous on what needed to be done while the clock was ticking. Under such an agreement, every country shall implement its own five-year climate action plan in a bid to ratchet up ambition levels. Developed countries vowed to provide significant amount of money as well as technical support to help under-developed countries cut down on Greenhouse Gas (GHG) emissions and adapt to climate change.